CHARACTERISTICS OF BAUXITE LATERITE DEPOSIT AND RARE EARTH ELEMENT AT HILL 16 AND HILL 30, TAYAN AREA, SANGGAU DISTRICT, WEST BORNEO - Sindhunata, Hugo
The study area is located at Mining Business Permit (IUP) of Tayan owned by PT. ANTAM UBPB, Sanggau District, West Kalimantan Province and bounded in the extent of 404522, 9986788 to 409060, 9991574 at UTM Zone 49S with WGS1984 datum (area of 21.5 km2). Samples of bauxite laterite are collected from 2 region which is Hill 16 and Hill 30. Hill 16 is located between coordinate of 404740, 9990467 to 405469, 9991396, and Hill 30 is located between coordinate of 407475, 9987395 to 407827, 9987754. Based on physiography units of Pontianak/Nangataman, the study area are included at low terrain, tight cut hills composed of granite and volcanic rocks at certain area. There are four stratigraphy units based on modified units from PT. ANTAM (sorted from oldest to youngest): phyllite unit, granodiorite unit, quartz diorite unit, and swamp deposits. This study is conducted to determine the characteristics of bauxite laterite at Hill 16 and 30, and to determine the correlation with the REE (Rare Earth Element) abundance. Data used are DEM (Digital Elevation Model), field data, and assay data. Assay data are examined by XRF (X-ray Fluorescence) and ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometry) using 18 bauxite laterite sample and one bedrock from Hill 16, and 18 bauxite laterite sample and 1 bedrock sample from Hill 30. Bauxite laterite deposit at Hill 16 and 30 generally can be distinguished by the bedrock characteristics. Bauxite laterite deposits at Hill 16 came from granodiorite while deposits at Hill 30 came from quartz diorite. The deposits at Hill 30 had undergo 3 stages of formation: clay formation zone, bauxite zone, and latosol zone. Clay formation zone is characterised by high SiO2 and R-SiO2 content and weak lateritization, bauxite formation zone characterised by high Al2O3 and Fe2O3 content and medium to strong lateritization, and the latosol formation zone is characterised by high TiO2 content and weak lateritization. In general, bauxite at Hill 16 area are Kaolinitic Bauxite, Bauxitic Kaolinite, and Bauxite, while at Hill 30 generally are Laterite and Bauxite. Generally, REE abundance of bauxite laterite deposit at Hill 16 and 30 are equally distributed in every zone, ?REE(La-Lu) enrichment towards bedrock, and ?LREE(La-Eu) content higher than ?HREE(Gd-Lu). Based on Pearson Coefficient analysis, the main factor of ?LREE(La-Eu) dan ?HREE(Gd-Lu) at Hill 16 is the Fe-minerals while at Hill 16 are P and Sr-minerals. The main factor of Sc at Hill 16 and 30 is the Fe-Minerals.